Subverting the Marriage-Amendment Crusade with Law and Policy Reform - Anita Bernstein (Washington University Journal of Law & Policy, 2007)
This Essay endorses diffusion, the path of a peaceful guerrilla movement, in the struggle against the placement of marriage bans into state constitutions. The guerrilla movement commended here hurts no one while doing subversion work more effectively than does the unity-and-clarity approach that the non-guerrilla same-sex marriage movement seems to prefer. Among single-subject slogan messages sent to nonpartisans in the United States, “family values” or “traditional marriage” seems to beat what the progressive side thinks is its goal: “civil rights,” “marriage equality.” For activists, coming together to write enlightened marriage policy reform and announce an agenda on websites wins publicity and builds camaraderie, but also forms a target for focused conservative reaction, not to say homophobic rage. As an alternative—or at least a supplement—to this common cause, marriage activists should scatter into different corners of law and policy to make marital status of less law-based consequence for individuals.
Keywords: U.S. states – marriage policies; Canadian Ministry of Justice – Beyond Conjugality (report); Same-sex marriage – Law & amp; legislation; Domestic relations law reform; Civil unions; Domestic partnerships; Families; Marriage; Defense of Marriage Act of 1996